2001
DOI: 10.1093/aje/153.4.372
|View full text |Cite
|
Sign up to set email alerts
|

Immigration and the Health of Asian and Pacific Islander Adults in the United States

Abstract: The authors used the 1992-1995 National Health Interview Survey to examine the effect of immigrant status (both nativity and duration of residence in the United States) on the health of Asian and Pacific Islander adults by constructing models in which national origin was also specified. In logistic regression models adjusted for age, marital status, living arrangement, family size, and several socioeconomic indicators, immigrants were found to be in better health than their US-born counterparts, but their heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(122 citation statements)
references
References 22 publications
5
112
1
4
Order By: Relevance
“…Self-rated physical health was measured by a question that asked respondents to rate their overall physical health (excellent, very good, good, fair and poor). Following conventional practice, we collapsed these categories into a dichotomized outcome with one indicating ''poor'' or ''fair'' physical health and zero otherwise (Cho et al, 2004;Frisbie et al, 2001). Physical discomfort was assessed based on one question asking how often respondents experienced physical discomfort in the past 30 days.…”
Section: Methodsmentioning
confidence: 99%
“…Self-rated physical health was measured by a question that asked respondents to rate their overall physical health (excellent, very good, good, fair and poor). Following conventional practice, we collapsed these categories into a dichotomized outcome with one indicating ''poor'' or ''fair'' physical health and zero otherwise (Cho et al, 2004;Frisbie et al, 2001). Physical discomfort was assessed based on one question asking how often respondents experienced physical discomfort in the past 30 days.…”
Section: Methodsmentioning
confidence: 99%
“…Migration has also marked the experiences of many elderly Asians (Parker Frisbie et al 2001). The consequences of migration may markedly differ for these groups, however, depending on the forces that prompted migration (for example, economic concerns, political turmoil, or family reunification); the characteristics of the community left behind (e.g.…”
Section: International Migrationmentioning
confidence: 99%
“…Research often describes the immigrant population as healthier than natives when they arrive in the host country and that, over time, their health declines (Chen et al 1996;McDonald and Kennedy 2004;Newbold 2005). Among Hispanics and Asians, studies have demonstrated a positive relationship between time in the U.S. and negative health outcomes such as low birthweight (Balcazar and Krull 1999;Scribner and Dwyer 1989), psychological distress (Kaplan and Marks 1990), and activity limitations (Cho et al 2004;Frisbie et al 2001). Prior work has also shown that the prevalence of characteristics such as obesity and overweight are positively associated with time in the U.S. (Goel et al 2004;Gordon-Larsen et al 2003;Himmelgreen et al 2003) and in Canada (Cairney and Ostbye 1999).…”
Section: Health Statusmentioning
confidence: 99%